The contemporary world - Acero, Allegro C.; Marquez, Celeste C.; Solmerano, Ernesto Thaddeus M. (Manila : Fastbooks Educational Supply, Inc., 2023)
"The Contemporary World is one of the core courses in the new General Education Curriculum (GEC) that all Philippine colleges and universities must offer. The course will look at current global conditions from both local and global perspectives. The objective of this course is to engage students in current global issues and problems that all of humanity confronts. The course book offers features which are designed to assist students to develop a theoretically informed and empirically grounded understanding of globalization through readings class discussions, writing, video viewing, and group presentations."
Includes references.
English.
Keywords: Globalization